The Development of Critical Consciousness and its Relation to Academic Achievement in Adolescents of Color - Seider, Scott; Clark, Shelby; Graves, Daren (Child development, 2020)
Critical consciousness, the process by which individuals come to understand, analyze, and take action against systems of oppression, is associated with several positive youth outcomes. However, little research has considered how the core components of critical consciousness (critical reflection, political agency, critical action) are associated with academic achievement. The present study explored the extent to which the developing critical consciousness of adolescents of color (N = 364) over 4 years of high school predicted academic achievement, as measured by grade point average (GPA) and the Scholastic Aptitude Test (SAT). Results demonstrated that adolescents’ critical reflection and critical action intercepts predicted SAT scores whereas critical reflection and critical action slopes predicted GPAs. Political agency was not predictive of either academic outcome.